2002
DOI: 10.1093/intimm/dxf028
|View full text |Cite
|
Sign up to set email alerts
|

The genes for perforin, granzymes A–C and IFN‐γ are differentially expressed in single CD8+ T cells during primary activation

Abstract: Here we show that the genes for perforin, the three major T cell granzymes (A-C) and IFN-gamma are differentially expressed during primary activation of naive CD8(+) T cells, kinetically and at the single-cell level. When CD44(low)CD62L(high)CD8(+) lymph node T cells were activated with IL-2 and immobilized antibodies to CD3, CD8 and CD11a, expression of perforin, granzyme B and IFN-gamma mRNAs was induced by day 2, and increased in parallel with perforin-dependent cytolytic activity. Granzyme C and A transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
86
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 47 publications
11
86
1
1
Order By: Relevance
“…Expression of perforin and IFN-c/TNF-a is also largely segregated. The genes for perforin, granzymes and IFN-c are also differentially expressed in naive CD8 + T cells during primary activation [29]. One explanation for this heterogeneity is a stochastic and independent regulation of individual effector molecules determined by the intensities of the stimulation during primary activation, as suggested by our study.…”
Section: Discussionsupporting
confidence: 59%
“…Expression of perforin and IFN-c/TNF-a is also largely segregated. The genes for perforin, granzymes and IFN-c are also differentially expressed in naive CD8 + T cells during primary activation [29]. One explanation for this heterogeneity is a stochastic and independent regulation of individual effector molecules determined by the intensities of the stimulation during primary activation, as suggested by our study.…”
Section: Discussionsupporting
confidence: 59%
“…These data support the notion that the different grz family members are regulated independently. Previous analysis of effector mRNA expression has demonstrated that there is heterogeneity of grz/pfp expression within virus-specific CTL, with little evidence of effector mRNA co-expression [7,8,12,25]. To date, this heterogeneity has not been examined at the protein level for murine virus-specific CTL.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR utilized 1 U of Taq polymerase (Invitrogen Life Technologies), 1.5 mM MgCl 2 , 0.2 mM dNTP, and 20 pmol each of the sense and antisense primers. The majority of the primers used to amplify each region have been described previously (26). Otherwise, the primers were: GzmK, EX sense 5Ј-GGCCATTTATGGCGTCC ATCCAG-3Ј, antisense 5Ј-TCACCTGGCATTTGGTCCCA-3Ј and IN sense 5Ј-GCAAGCATATTTGTGGAGGA-3Ј, antisense 5Ј-GTCGTGAG AATGGGATGAAC-3Ј; CD8␣, EX sense 5Ј-ATGGACGCCGAACTTGG TCA-3Ј, antisense 5Ј-GTTCGCAGCACTGGCTTGGT-3Ј, IN sense 5Ј-GTC AGAAGGTGGACCTGGTATG-3Ј, antisense 5Ј-GAACTTGTTCAGGGT GAGAACG-3Ј.…”
Section: Single-cell Sorting and Rt-pcrmentioning
confidence: 99%
“…After polyclonal in vitro stimulation of naive CD8 ϩ T cells, early transcription of Pfp and GzmB mRNA is followed by GzmA mRNA expression 3-4 days later (26). The single-cell effector mRNA profiles were very heterogeneous, suggesting that Gzm and Pfp transcription may not be coregulated (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation